P219 IS DISPROPORTIONALITY ENOUGH TO IDENTIFY CANDIDATES FOR PERCUTANEOUS MITRAL VALVE REPAIR? A CLINICAL CASE. (18th May 2022) - Carassia, C; Mennuni, M; Degiovanni, A; De Vecchi, S; Erbetta, R; Patti, G
Abstract: Functional mitral regurgitation (FMR) is defined as regurgitation with structurally normal leaflets secondary to the distortion of the LV in the context of dilated cardiopathy. The conflicting results emerged from the MITRA–FR and COAPT trials have raised a new interest in the individuation of "primary–like" components of MR. In this scenario, a binary classification in proportionate and disproportionate FMR has been proposed by Garland et al. When the MR is completely due to LV remodeling, they observed a linear relationship between ERO and LVEDV, defining a proportionate FMR; on the other side, when the ERO is superior to the expected one, the FMR is considered as disproportionate, and it may benefit from TEER on top of GMDT. However, the Garland's model may not explain the full complexity of MV apparatus and FMR. We present the case of a 75–years–old woman diagnosed with dilated cardiopathy of ischemic origin, known since 2008. In 2021 she started receiving multiple hospitalizations for acute decompensation of HF with dyspnoea and symptoms of hypoperfusion, such as AKI on top of CKD and hypotension. The TOE showed a severe LV dysfunction and a moderate dilation of the left ventricle (EF 19%, LVEDVi 90 ml/m2), with a severe FMR secondary to annular dilation and retraction with tethering of the posterior leaflet (MR ERO 0, 27 cm2, VC 0, 67 cm, RV 45 ml). In order to improve symptoms she underwent TEER with implantation of one Edwards Pascal device at the level of A2–P2, with good results and a mild residual MR. Basing on the Garland's model our patient would have been classified as proportionate FMR, with no benefit from TEER. However, removing MR component from the heart disease, she improved her stroke volume and her systolic function, allowing a better peripheral perfusion, as showed by an increase in renal function and in arterial pressure during follow–up, which allowed an introduction ad up–titration of Sacubitril/Valsartan, impossible before TEER. At the same time TEER decreased pulmonary pressures improving dyspnoea and functional status (she was NYHA II–III at the 6 month follow–up). In conclusion, the binary model of proportionality has the strength of being easy–to–use and of easily recognizing a primary–like MR that can benefit from TEER; however, proportionate FMR probably includes different pathophysiological mechanisms of disease, requiring an ultra stratification to better identify cases where TEER may increase survival.